P-024 Dual-energy CT-based characterization of experimental human clot analogues with different compositions created under dynamic flow conditions: an in vitro stroke study. (22nd July 2018) - Fitzgerald, S; Rizvi, A; Michalak, G; Kadirvel, R; Doyle, K; Brinjikji, W; Kallmes, D
Abstract : Background and purpose: Study investigators have demonstrated the utility of CT to characterize different clot compositions among patients with acute ischemic stroke (AIS) for preclinical evaluation of endovascular embolectomy devices. To this end, device selection can be optimized with accurate characterization of embolus in large vessel occlusions in these patients. Further still, prior data suggests increased clot attenuation with red blood cell (RBC) content on non-contrast CT scan. Nevertheless, there is paucity of evidence-based data for dual-energy CT-based characterization of human clot analogues created under dynamic flow conditions with different clot compositions to simulate various stroke etiologies. We therefore performed an in vitro study to optimize human clot characterization utilizing non-contrast dual-energy CT. Methods: Experimental clot analogues of varying compositions of RBCs and fibrin were created from fresh human blood. A modified chandler loop system was used for creation of these clots to simulate in-vivo dynamic flow conditions. The fresh human clot analogues were subsequently scanned with a second-generation dual source scanner (Siemens Definition Flash) using dual-energy head CT protocol (80/Sn 140 kV). Virtual mono-energetic images at 50 keV were generated from the dual-energy data. A region of interest (ROI) was placed over each clot phenotype and mean clot attenuation was measured. The composition of each clot composition was histologically verified using Hematoxylin and Eosin staining. Results: Eight fresh human clot analogues of varying compositions were generated in an increasing fashion of RBC content with corresponding decreasing fibrin content (RBC content: 3.83%, 4.07%, 22.41%, 24.31%, 42.31%, 51.79%, 54.91%–60.82%, respectively). Non-contrast dual-energy CT allowed for significantly improved discrimination among RBC-rich and fibrin-rich clot analogues based on Hounsfield Unit (HU) Density (R 2 =0.9288, p<0.01). Conclusions: A non-contrast dual-energy CT with 80/Sn 140 kV provided significant differentiation among varying RBC-rich and fibrin-rich in vitro human emboli. Further studies are warranted to validate these findings. Disclosures: S. Fitzgerald: None. A. Rizvi: None. G. Michalak: None. R. Kadirvel: None. K. Doyle: None. W. Brinjikji: None. D. Kallmes: None.